2018
DOI: 10.1002/app.46468
|View full text |Cite
|
Sign up to set email alerts
|

Green esterification: A new approach to improve thermal and mechanical properties of poly(lactic acid) composites reinforced by cellulose nanocrystals

Abstract: Cellulose nanocrystal (CNCs)‐reinforced poly(lactic acid) (PLA) nanocomposites were prepared using twin screw extrusion followed by injection molding. Masterbatch approach was used to achieve more efficient dispersion of CNCs in PLA matrix. Modified CNCs (b‐CNCs) were prepared using benzoic acid as a nontoxic material through a green esterification method in a solvent‐free technique. Transmission electron microscopy images did not exhibit significant differences in the structure of b‐CNCs as compared with unmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The formation of cross-linking in the polymer matrix hinders the untangling of the polymer chains and the sliding over each other after the glass transition temperature in the rubbery state [28]. In the DMA test, the mobility of the polymer chains is a response against the dynamic deformations of a particular frequency, and the viscoelastic properties of the polymers can be evaluated through the peak values of the tanδ curves [29]. Surprisingly, the recycled Solanyl displayed a lower tanδ peak intensity as compared with virgin Solanyl, suggesting, fewer polymer chains participate in the transition from a glassy to a rubbery state.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of cross-linking in the polymer matrix hinders the untangling of the polymer chains and the sliding over each other after the glass transition temperature in the rubbery state [28]. In the DMA test, the mobility of the polymer chains is a response against the dynamic deformations of a particular frequency, and the viscoelastic properties of the polymers can be evaluated through the peak values of the tanδ curves [29]. Surprisingly, the recycled Solanyl displayed a lower tanδ peak intensity as compared with virgin Solanyl, suggesting, fewer polymer chains participate in the transition from a glassy to a rubbery state.…”
Section: Resultsmentioning
confidence: 99%
“…Reinforcement of high melting temperature polymers with modified biomass has extensively been reported [6][7][8][9][10][11]. Likewise, it has also been extensively reported that the addition of cellulose fibrils in various forms to produce polymeric composites can greatly enhance mechanical properties of the base polymeric materials at significantly lower loadings compared to other biomasses [12][13][14][15][16][17]. Forms of cellulose fibrils can range from cellulose powders to microcrystalline cellulose and nanocrystalline cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…α‐Cellulose has a large number of hydroxyl groups, which are the main basis for hydrogen interactions between two nanofibrils and produce gel‐like structures and the dispersion of hydrophilic cellulose in hydrophobic polymer matrixes; they also serve as an obstacle to better interfacial adhesion between the components of the final composites . To increase the compatibility between α‐cellulose and the polymer matrix, α‐cellulose can be modified physically or chemically . A favorable solution is the chemical surface modification of α‐cellulose to reduce the number of hydroxyl interactions and to increase its compatibility with different matrixes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] To increase the compatibility between α-cellulose and the polymer matrix, α-cellulose can be modified physically or chemically. [17][18][19] A favorable solution is the chemical surface modification of α-cellulose to reduce the number of hydroxyl interactions and to increase its compatibility with different matrixes. Recently, several chemical methods, including ringopening polymerization, atom transfer radical polymerization, reversible addition fragmentation chain-transfer polymerization, nitroxide-mediated polymerization, and single electron transferliving radical polymerization, have been used to modify cellulose surfaces.…”
Section: Introductionmentioning
confidence: 99%